The impact of gut microbiome on neuro-autoimmune demyelinating diseases - Pouria Abolfazli; Cristina Nkene Apue Nchama; Brandon Lucke-Wold (Academia Biology)
Demyelinating diseases, including multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and chronic inflammatory demyelinating polyneuropathy (CIDP), are characterized by dysregulated immune responses to self-antigens, leading to myelin loss. Genetic predisposition and environmental factors, such as alterations in the gut microbiome, influence these conditions. We have examined studies on gut microbiome in patients and animal models and reviewed the existing literature on this topic. Germ-free mice showed a reduced susceptibility to demyelinating disorders, highlighting the crucial role of gut bacteria in disease development. Gut dysbiosis promotes the generation of proinflammatory Th17 cells, contributing to blood–brain barrier (BBB) disruption and central nervous system (CNS) autoimmunity. In MS, an increased presence of Th17 cells correlates with disease severity, accompanied by elevated levels of Streptococcus and a higher Firmicutes/Bacteroidetes ratio. Moreover, dysbiosis in MS involves more pathogenic bacteria and fewer beneficial taxa, further influencing disease progression. Similarly, NMOSD exhibits gut microbiota alterations linked to disease severity, with Streptococcus and Clostridium perfringens being significant contributors, suggesting a gut–CNS interaction in pathogenesis. Prebiotic and probiotic interventions can modify gut microbiota, reduce inflammatory markers, and improve patient outcomes, indicating the therapeutic potential of targeting gut microbiota in managing MS. In conclusion, gut microbiome serves as a primary risk factor in developing demyelinating diseases by producing toxins and metabolites that facilitate communication between the gut and brain. Understanding these relationships provides potential therapeutic approaches targeting gut microbiota to more effectively manage and alleviate demyelinating diseases.